2014
DOI: 10.1097/mcp.0000000000000063
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial valve placement for the treatment of bronchopleural fistula

Abstract: The use of endobronchial valves for the treatment of bronchopleural fistula is well tolerated and effective. Controlled clinical trials are needed to further evaluate their efficacy and identify ideal patient populations for their use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 38 publications
0
22
0
1
Order By: Relevance
“…310,326 Newer, non-invasive bronchoscopic approaches using valves and other methods might offer alternative approaches in selected patients who refuse surgery or are not surgical candidates. 327 Surgical mortality is <5%, but the rate of complications varies between 12% and 30%. 295 Several questions remain unanswered, including timing of surgery, use of adjunctive therapy, and optimal investigation in those patients with borderline lung function who might be eligible for surgery, and these have been reviewed in detail by Calligaro and colleagues.…”
Section: Surgical Managementmentioning
confidence: 99%
“…310,326 Newer, non-invasive bronchoscopic approaches using valves and other methods might offer alternative approaches in selected patients who refuse surgery or are not surgical candidates. 327 Surgical mortality is <5%, but the rate of complications varies between 12% and 30%. 295 Several questions remain unanswered, including timing of surgery, use of adjunctive therapy, and optimal investigation in those patients with borderline lung function who might be eligible for surgery, and these have been reviewed in detail by Calligaro and colleagues.…”
Section: Surgical Managementmentioning
confidence: 99%
“…K E Y W O R D S : non-pharmacological treatment of TB; EbV; anti-tuberculosis treatment; bronchoscopy DATA REGARDING THE APPLICATION of an endobronchial valve (EbV) in treating various pulmonary diseases have recently been published in the medical literature. This drug-free, minimally invasive method is used to reduce lung volume in patients with pulmonary emphysema, [1][2][3] to treat pneumothorax in patients with bronchopleural fistulas and/or in postoperative patients, [4][5][6][7][8][9] and to treat spontaneous pneumothorax of different aetiologies. 10 In Russia, EbV has been used to treat patients with various forms of destructive pulmonary tuberculosis (PTB).…”
Section: O N C L U S I O N Smentioning
confidence: 99%
“…Most patients suffered from post-operative PAL, suppurative lung disease or spontaneous pneumothorax [3]. To date, there exists only one report in the current literature about EBV treatment of PAL secondary to pneumocystis jirovecii pneumonia [4].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, EBV treatment for pneumothorax secondary to PAL was found to be effective and well-tolerated with resolution rates between 48 and 100% and rare complications like infection, expectoration or migration of the valves [3]. However, in most previous case reports, EBVs were removed four to eight weeks after resolution of the PAL in order to minimise the risk of side effects [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation